Drug-Induced Thrombocytopenia following a Transvaginal Oocyte Retrieval for In Vitro Fertilization - Ioanna A. Comstock; Michelle Longmire; Richard H. Aster; Amin A. Milki (Case Reports in Obstetrics and Gynecology)
Drug-induced immune thrombocytopenia has been associated with hundreds of medications and can lead to devastating consequences for the patient. We present a case of a healthy 33-year-old female undergoing in vitro fertilization who developed a severe drug-induced thrombocytopenia, petechiae, and a large hemoperitoneum after receiving Cefazolin antibiotic prophylaxis for a transvaginal oocyte retrieval. The patient was admitted to the intensive care unit for resuscitation with blood products. The presence of drug-dependent platelet antibodies to Cefazolin was confirmed serologically.